Aspirin in COVID-19: Pros and Cons - Zareef, Rana; Diab, Marwa; Al Saleh, Tala; Makarem, Adham; Younis, Nour K.; Bitar, Fadi; Arabi, Mariam (Frontiers in Pharmacology, 2022)
Since its emergence, the COVID-19 pandemic has been ravaging the medical and economic sectors even with the significant vaccination advances. In severe presentations, the disease of SARS-CoV-2 can manifest with life-threatening thromboembolic and multi-organ repercussions provoking notable morbidity and mortality. The pathogenesis of such burdensome forms has been under extensive investigation and is attributed to a state of immune dysfunction and hyperinflammation. In light of these extraordinary circumstances, research efforts have focused on investigating and repurposing previously available agents that target the inflammatory and hematological cascades. Aspirin, due to its well-known properties and multiple molecular targets, and ought to its extensive clinical use, has been perceived as a potential therapeutic agent for COVID-19. Aspirin acts at multiple cellular targets to achieve its anti-inflammatory and anti-platelet effects. Although initial promising clinical data describing aspirin role in COVID-19 has appeared, evidence supporting its use remains fragile and premature. This review explores the notion of repurposing aspirin in COVID-19 infection. It delves into aspirin as a molecule, along with its pharmacology and clinical applications. It also reviews the current high-quality clinical evidence highlighting the role of aspirin in SARS-CoV-2 infection.